PENGGUNAAN POLYETHYLENE GLYCOLE SEBAGAI MEDIA SIMULASI CEKAMAN KEKERINGAN TERHADAP VIABILITAS DAN VIGOR BEBERAPA VARIETAS BENIH KACANG TANAH (Arachis hypogaea L.) PADA STADIA PERKECAMBAHAN - Halimursyadah Halimursyadah; Agam Ihsan Hereri; Aira Hafnizar (Jurnal Floratek, 2013)
This study was aimed at determining peanut varieties that are tolerant to drought stress and assessing the effectiveness of the use of PEG 4000 as a media simulation to drought stress.  Experiment was arranged in a Completely Randomized Design (CRD) factorial 4 x 4, repeated three times. First factor was variety, consisted of four levels, namely Tuban, Bima, Bison and Local Aceh. Second factor was PEG concentration, consisted of 4 levels, namely control, 3.5%, 11.6%, and 18.1%. Variables measured were maximum growth potential, germination rate, relative growth rate, vigor index, germination value, root length, hypocotyl length, and seedling dry weight.  The results showed that varieties exerted significant effects on maximum growth potential, germination rate, relative growth rate, root length, and hypocotyl length. PEG concentration exerted significant effects on maximum growth potential, germination rate, growth velocity, relative vigor index, germination value, root length, hypocotyl length, and seedling dry weight. There were interactions between varieties and PEG concentration on relative growth rate, root length, and hypocotyl length of groundnut seeds. Local variety of Aceh was recommended as a tolerant variety to drought stress.  Bison was not tolerant to drought stress. Bima was recommended as a moderate tolerant variety to drought, while Tuban was a tolerant variety to drought.